Small Activating RNA Modulation of the G Protein‐Coupled Receptor for Cancer Treatment (Adv. Sci. 26/2022). Issue 26 (15th September 2022) - Xiong, Yunfang; Ke, Ran; Zhang, Qingyu; Lan, Wenjun; Yuan, Wanjun; Chan, Karol Nga Ieng; Roussel, Tom; Jiang, Yifan; Wu, Jing; Liu, Shuai; Wong, Alice Sze Tsai; Shim, Joong Sup; et al.
Abstract : Small Activating RNA Modulation In article number 2200562, Ling Peng, Leo Tsz On Lee, and co‐workers, report for the first time that small activating RNA (saRNA) delivered by amphiphilic dendrimer can effectively modulate a G protein‐coupled receptors (GPCR), Mas receptor, for cancer treatment. This project provides not only a new strategy for cancer therapy, but also a new avenue to address undruggable GPCRs.